Biocompatibilty of starch-based films from starch of Andean crops for biomedical applications - Torres, F.G.; Troncoso, O.P.; Grande, C.G.; Díaz, D.A. (Elsevier, 2011)
In this communication we report the use of starch films as cell substrates. To the best of our knowledge it is the first time that films prepared from native Andean starches are studied as biomaterials. For the present study 3T3 fibroblast cells were seeded in seventeen novel starch based films from different Andean crops. In order to analyze the use of these types of starch as biomedical materials, biocompatibility, viability and cell adhesion studies were performed at the third day of incubation on supplemented DMEM medium. After cultured, films made from starch of “tunta”, “muro-huayro” potato and white carrot showed the highest level of living cells and cell viability. These results indicate that native starches from Andean crops can be used for biomedical applications.
Keywords: Native starch; Andean crops; Biomedical applications; https://purl.org/pe-repo/ocde/ford#2.11.01